Mapping the mitochondrial landscape in T2DM: key findings from 2003-2023 - Tan, Yi; Liu, Mingjun; Zhou, Xinfeng; Gao, Tianjiao; Fang, Jinxu; Wang, Sixian; Chen, Shaotao (Frontiers in Endocrinology, 2024)
Backgound: T2DM, a chronic metabolic disorder, poses a significant threat to global public health. Mitochondria play a crucial role in the pathogenesis of T2DM. This study intends to investigate the correlation between mitochondria and T2DM over the past two decades (2003-2023) through bibliometric analysis. Its objectives are to pinpoint trends, emphasize research priorities, and establish a foundation for future investigations. Methods: A literature search was conducted using the SCI-E database. All recorded results were downloaded in plain text format for further analysis. The following terms were analyzed using Vosviewer 1.6.18, citespace 6.3r1, bibliometrix in RStudio (v.4.4.1), and Microsoft Excel 2021: country, institution, author, journal, references, and keywords. Results: From January 1, 2003 to December 31, 2023, a total of 2,732 articles were retrieved. The United States, China, and Italy contributed most of the records.UNIVERSITY OF CALIFORNIA SYSTEM, INSTITUT NATIONAL DE LA SANTE ET DE LA RECHERCHE MEDICAL INSERM, and US DEPARTMENT OF VETERANS AFFAIRS were the top 3 most productive institutions. rocha milagros, victor victor m had the most publications, followed by roden michael, and petersen kf had the most citations together. DIABETES published the most articles on research on this topic, followed by AMERICAN JOURNAL OF PHYSIOLOGY-ENDOCRINOLOGY AND METABOLISM,DIABETOLOGIA. The key points of this topic are the relationship between mitochondria and T2DM, the skeletal muscle mitochondrial changes observed in T2DM, and the impact of mitochondrial dysfunction on T2DM. Over the past five years, particle dynamics, mitochondrial dysfunction, and mechanism research have emerged as significant focal points in this field. Conclude:This paper successfully identified the key areas and emerging trends in the relationship between mitochondria and T2DM, thereby offering valuable insights for future research.